Pengenalan dan Pelatihan Literasi Digital Bagi Mahasiswa STIE Makassar Maju - Runimeirati Runimeirati; Abdul Sakti; Nurfadila Nurfadila (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This Community Service is carried out at STIE Makassar Maju with the target activity being students. These students were introduced to digital literacy and how to use digital literacy in the future. Before this community service was implemented, only around 20% understood digital literacy, and after this community service was implemented, an increase of up to 70% of students were able to recognize and use digital literacy in a simple way. The reason for choosing this topic is because digital literacy is currently very popular among young people, especially students. Digital literacy skills are very important in the 5.0 era. The method used is a persuasive method which focuses on a direct approach to participants.